Second Primary Malignancies in Patients With Hepatocellular Carcinoma: A Population-Based Analysis - Kong, Junjie; Yu, Guangsheng; Si, Wei; Li, Guangbing; Chai, Jiawei; Liu, Yong; Liu, Jun (Frontiers in Oncology, 2021)
Background: Second primary malignancy (SPM) is becoming a threaten for health of cancer survivors. However, data on the features and results of patients with hepatocellular carcinoma (HCC) with SPMs were scarce. This study aimed to explore the characteristics of HCC patients with SPMs and to screen HCC patients at high risk of developing SPMs. Method: HCC patients diagnosed between 2000 and 2014 in the Surveillance, Epidemiology, and End Results (SEER) database were retrospectively analyzed. Eligible patients were divided into only one primary malignancy and SPM groups. The Fine-Gray proportional subdistribution hazards model was used to explore risk factors of developing SPMs and a competing-risk model was established to predict the probability of developing SPMs for HCC patients after initial diagnosis. The calibration curves, concordance index (C-index) and decision curve analysis (DCA) were used to evaluate the performance of the nomogram. Results: A total of 40314 HCC patients were identified, 1593 (3.95%) of whom developed SPMs 2 months after initial diagnosis with a maximum follow-up time of approximately 18 years. The 3-, 5- and 10-year cumulative incidence of SPMs were 2.35%, 3.12% and 4.51%, respectively. Age at initial diagnosis, extent of disease, tumor size and treatment were identified as independent risk factors of developing SPMs and integrated into the competing-risk nomogram. The C-index of the nomogram was 0.677 (95% confidence interval 0.676-0.678) and the calibration curves showed excellent agreement between the nomogram prediction and the actual observations. Furthermore, DCA indicated that the nomogram had good net benefits in clinical scenarios. Conclusions: HCC survivors remain at high risk of developing SPMs. The development of SPMs was associated with clinical features and treatment strategies. A competing-risk nomogram was constructed to help surgeons identify patients at high risk of developing SPMs and contribute further management of SPMs.